Design and build multiple input multiple output (MIMO) wideband element microstrip antennas for WiFi access-point applications - Maria, Popy; Asril, Aprinal Adila; Nasrul, Nasrul; Nita, Sri; Yuhanef, Afrizal (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Technology in the telecommunications sector continues to develop. One of them is the Multiple Input Multiple Output (MIMO) antenna used in WIFI access oint application using MIMO technique in enhancement the need to transfer large amounts of data. In the design and manufacture of MIMO antennas for WIFI access applications point with dimensions of 110 mm x 112 mm using FR-4 substrate specifications with a thickness of 1.6 mm. The antenna consists of four ports and is at each corner The groundplane has four slots to achieve good isolation and produces good bandwidth. The antenna simulation produces a bandwidth of 1.0516 GHz with frequency 2.4 GHz, return loss -12.78 dB, isolation -16.08 dB, and VSWR 1.53 dB. Meanwhile, manufactured antennas produce a bandwidth of more than 100 MHz with frequency 2.4 GHz, return loss -13.5 dB, isolation -18.8 dB, and VSWR 1.29 dB. Antenna simulation using the CST Studio Suite 2019 software application. In the application of the antenna used for Wi-Fi as a transmitter By comparing distances, different results are obtained where the power value is Each distance is different because the farther the distance, the greater the power value produced or emitted will be smaller or less optimal network.